Analisis Semiotika Tokoh Chelsey Sullenberg dalam Film Sully - Kiran Muhammad iqbal; M.E Fuady (UNISBA Press, 2022)
Abstract. Film is one of the means of mass media communication that can be enjoyed by many audiences. This is because in addition to being a means for mass communication, films are also works that are used as a means of entertainment and education that can be enjoyed by understanding the storyline to the message or meaning of the film. A leadership crisis does not mean that there are no leaders. In 2009 a tragedy that will always happen that happened on the Hudson river. US Airways A320 with captain Chesley accompanied by co-pilot Jefferey had to do it in the middle of the Hudson river. This research is entitled Representation of Chesley Sullenberg's Leadership in Sully Film (John Fiske's Semiotics Analysis). This study uses a qualitative method with John Fiske's semiotic approach. The purpose of this research is to know reality, representation, and ideology. The results in this study conclude that at the level of reality Sully's behavior as a pilot in Sully's film can run as a professional leader, adhere to ideology as a leader and understand human relationships to solve problems. Sully tends to be professional as a leader who always looks presentable in public and during the event. At the level of representation in the form of camera codes and dialogue codes that cover various shooting techniques in Sully's film, there is no difference from other films. The visible shots are Framing with background, Group shot, Walking Shot, Two Shot, Three Shot, Eye Level, and Point of View Shot. The dialogue used by Sully in this film also really shows the role of leadership which shows that he is a leader who has an ideology and is professional by conducting persuasive communication to achieve goals. At the ideological level, the ideology that appears in Sully's film sees the ideology of a good leader in making every decision, the answers to decisions taken, and the ability to solve problems supported by knowledge of human relations. Sully is a representation of a professional leader who can be seen from his professionalism in carrying out his duties as a leader and his contribution to world aviation. Researchers also found that Sully applies ethical leadership theory which is seen through the way a leader leads behavior based on norms. The theory used in this research is the theory of sequence of cognition and the theory of S-R. This type of research is quantitative research, the method used is correlational quantitative method. The respondents in this study were Fikom Unisba 2017 students who knew Zaskia Sungkar as the brand ambassador of Wardah products. The sampling technique used is simple random sampling. Sampling using the Slovin formula and obtained as many as 65 respondents. Abstrak. Film merupakan salah satu sarana komunikasi media massa yang dapat dinikmati oleh banyak khalayak. Hal tersebut karena selain sarana untuk komunikasi massa, film juga merupakan karya yang dijadikan sarana hiburan dan edukasi yang dapat dinikmati dengan memahami alur cerita hingga pesan atau makna dari film tersebut. Krisis kepemimpinan bukan berarti tidak terdapat sosok pemimpin. Pada tahun 2009 terjadi sebuah tragedi yang akan selalu teringat yaitu keajaiban di sungai Hudson. US Airways A320 dengan kapten Chesley yang bertugas ditemani oleh kopilot Jefferey harus melakukan pendaratan ditengah sungai Hudson. Penelitian ini berjudul Representasi Kepemimpinan Tokoh Chesley Sullenberg dalam Film Sully (Analisis Semiotika John Fiske). Penelitian ini menggunakan metode kualitatif dengan pendekatan semiotika John Fiske. Tujuan dari penelitian ini adalah untuk mengetahui realitas, representasi, dan idelogi. Hasil dalam penelitian ini menyimpukan bahwa pada level realitas perilaku Sully selaku pilot pada film Sully yang dapat menjalankan sebagai pemimpin yang professional, memegang teguh ideologi sebagai pemimpin dan memahami human relations untuk memecahkan permasalahan. penampilan Sully cenderung professional sebagai seorang pemimpin yang selalu terlihat rapih dihadapan publik dan saat sedang bertugas. Pada level representasi dalam bentuk kode kamera dan kode dialog yang meliputi berbagai teknik pengambilan gambar dalam film Sully tidak memiliki perbedaan dengan film lainnya. Pengambilan gambar yang terlihat yaitu, Framing with background, Group shot, Walking Shot, Two Shot, Three Shot, Eye Level, dan Point of View Shot. Dialog yang di gunakan oleh Sully dalam film ini juga sangat menunjukan peran kepemimpinan yang menunjukan bahwa ia merupakan seorang pemimpin yang memiliki ideologi dan professional dengan melakukan komunikasi persuasif untuk mencapai tujuan. Pada level ideologi terlihat Ideologi yang muncul dalam film Sully memperlihatkan ideologi seorang pemimpin yang baik dalam pengambilan setiap keputusan, pertanggung jawaban atas keputusan yang diambil, serta kemampuan untuk menyelesaikan permasalahan yang didukung dengan pengetahuan mengenai human relations. Sully merupakan representasi dari seorang pemimpin profesional yang dapat dilihat dari profesionalisme dalam menjalankan tugas sebagai seorang pemimpin serta kontribusinya dalam dunia penerbangan. Peneliti juga menemukan bahwa Sully menerapkan teori kepemimpinan etis yang terlihat melalui cara seorang pemimpin memimpin perilaku berdasarkan norma.